HIV and Cryptococcal Meningitis: A Case Report - Djaputra, Edith maria (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2024)
Cryptococcal Meningitis (CM) has caused high morbidity and mortality rate among people living with HIV infection (PLWH). This case report showed a 32 years old female with HIV infection who came with chief complaint headache since 1 month before hospital admission (SMRS). Her headache had become worse in the past 2 days SMRS. Had been taking antiretroviral (ARV) therapy for 2 weeks and anti-toxoplasmic therapy for 3 weeks SMRS could not alleviate her complaints. Although the cerebrospinal fluid (LCS) examination has shown high probable Tuberculosis and Cryptococcal meningitis, specific examination for these infections only showed a positive result for CM. Few days after hospital admission, the patient experienced generalized seizures, monoplegia and sixth nerve palsy. Two months after high dose fluconazole therapy, the specific examination for Cryptococcal infection in CSF showed a negative result. This case report will show the difficulties in diagnosing and managing CNS opportunistic infections. Diagnosing CNS opportunistic infections, such as CM, has been a great challenge because of the low sensitivity and positive prediction value of the tests available, especially among PLWH. Managing these infections also poses some limitations, especially for the availability of their medications. Time to start ARVs has also been a big issue since ARVs were being given before 1definite diagnosis was established. This case study also showed that fluconazole alone can be used as an alternative therapy to amphotericin B and flucytosine for C.M. Therefore, this case report has shown the difficulty in diagnosing and managing CM in Indonesia.